Adaptation and applicability of an economical assessment methodology applied to the Cahuita National Park, Costa Rica - Marcondes, M.A.P. (1980)
Mapas. 78 ref. Sum. (En, Es). También en microficha *IICA, Turrialba (Costa Rica)